Análisis de indicadores para el uso sostenible de los recursos naturales de la Comunidad Cune del cantón Chilla - Flores Bernal, Julio César (My University, 2021)
This research work analyzes the different sustainability indicators with the bibliographic review of data and information from the Cune community as a study area with a qualitative approach and the use of the PER model for the selection of indicators used by entities such as Spain, Mexico, Latin America and the caribbean. The representative indicators for the community where the methodology is developed are established as a result reflect the need to solve the identified problems, the strategic guidelines for the sustainable development of the community are presented, established with the three dimensions of sustainable development with the purpose of improving the social perspective and natural resources with a regulated use of environmental services without harming future generations. The development of the work denotes the negative effects of the productive activities of the community that are derived from the agricultural and livestock activity for own consumption and commercialization. The use of the indicators is the means to measure the sustainability and sustainability of the area where a state response pressure matrix was made assimilating the cause and effect in order to find solutions and guidelines that improve the community's situation. The results are of importance for the follow-up of what is proposed, such as soil conservation strategies, among others, the relevant objectives present in the manual protecting what is ours by Eckart Boege are established for community planning and sustainable use of natural resources and seeking the good living of the community.
El presente trabajo de investigación analiza los diferentes indicadores de sustentabilidad con la revisión bibliográfica de datos e información de la comunidad de cune como área de estudio con enfoque cualitativo y la utilización del modelo PER para la selección de indicadores empleados por entidades como España, México, Latinoamérica y el caribe. Se establecen los indicadores representativos para la comunidad donde se desarrolla la metodología como resultado reflejan la necesidad de resolver los problemas identificados, se presenta los lineamientos estratégicos para el desarrollo sostenible de la comunidad entablado con las tres dimensiones del desarrollo sustentable con el propósito de mejorar la perspectiva social y recursos naturales con un aprovechamiento regulado de los servicios ambientales sin perjudicar a las generaciones futuras. El desarrollo del trabajo denota los efectos negativos de las actividades productivas de la comunidad que se derivan desde la actividad agrícola y pecuaria para consumo propio y de comercialización. El uso de los indicadores es el medio para medir la sostenibilidad y sustentabilidad del área en donde se realizó una matriz de presión estado respuesta asimilando la causa y efecto con el fin de buscar soluciones y lineamientos que mejoren la situación de la comunidad. Los resultados son de importancia para el seguimiento de lo propuesto como las estrategias de conservación de suelo entre otras se establece los objetivos relevantes presentes en el manual protegiendo lo nuestro de Eckart Boege para una planificación comunitaria y uso sostenible de los recursos naturales y buscando el buen vivir de la comunidad.
Keywords: INDICADOR; ORDENAMIENTO; COMUNIDAD; SUSTENTABILIDAD